Effects of Respiratory Muscle Strength Training on Respiratory-Related Impairments of Parkinson's Disease - Zhuang, Jinyang; Jia, Jie (Frontiers in Aging Neuroscience, 2022)
In addition to typical motor dysfunction, Parkinson's disease is also characterized by respiratory-related dysfunction. As a means of rehabilitation, respiratory muscle strength training (RMST) has been applied to restore Parkinson's disease (PD) functions. However, the current clinical value of RMST in the application for PD has not been widely established. This article aims to review the research progress of the application of RMST in PD rehabilitation to provide new sight into respiratory-related impairments management in people with PD.